Meeting Review: Diffuse X-Ray Scattering to Model Protein Motions - Wall, Michael E. (2014)
Problems in biology increasingly need models of protein flexibility to understand and control protein function. At the same time, as they improve, crystallographic methods are marching closer to the limits of what can be learned from Bragg data in isolation. It is thus inevitable that mainstream protein crystallography will turn to diffuse scattering to model protein motions and improve crystallographic models. The time is ripe to make it happen.